2014
DOI: 10.2147/jmdh.s57117
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the quality of advice provided by patent medicine vendors to users of oral contraceptive pills in urban Nigeria

Abstract: IntroductionIn Nigeria about 50% of oral contraceptive pill users obtain their products from proprietary patent medicine vendors (PPMVs). This group of service providers are poorly trained and have very limited knowledge about contraception. This paper investigated the nature of the advice offered to simulated current and potential users of oral contraceptive pills. The main objective was to assess the nature and quality of advice provided by PPMVs to pill users.MethodThis study is based on findings from a ‘my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
(30 reference statements)
1
9
0
Order By: Relevance
“…Studies on family planning services at PPMVs found similarly limited counseling for customers. Mystery client visits indicated that less than 15% of customers purchasing birth control pills were informed about side effects [ 40 , 78 ]. Some PPMVs expressed the need to maintain good communications, discretion, and confidentiality when dispensing family planning products to young customers [ 63 ], however others indicated that they may exclude youth and unmarried customers from receiving family planning services [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies on family planning services at PPMVs found similarly limited counseling for customers. Mystery client visits indicated that less than 15% of customers purchasing birth control pills were informed about side effects [ 40 , 78 ]. Some PPMVs expressed the need to maintain good communications, discretion, and confidentiality when dispensing family planning products to young customers [ 63 ], however others indicated that they may exclude youth and unmarried customers from receiving family planning services [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…For family planning, 51% of PPMVs self-reported referring clients to health facilities for related services [ 61 ]. Yet two mystery client studies found that only 30% to 45% of PPMVs referred first-time users, and about 50% referred current users experiencing contraceptive-related complications [ 40 , 78 ]. Low rates of referral were also documented for customers with TB.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As reported by the National demographic health survey, nearly half (41%) of contraceptives users in Nigeria obtain their contraceptives from the private sector, with more than half of all mothers/guardians seeking care from this sector for childhood illness such as Diarrhea (54.1%) and Fever (57.7%) [19]. Major reasons noted for this occurrence in several studies include the absence of formalities, reduced waiting time at the Medicine shop, the proximity of the outlets to clients, and the perception of clients that they will pay more at a health facility [20][21]. Patent and Proprietary Medicine Vendors (PPMVs) are increasingly being recognized as important providers of health commodities, as interest continues to grow among policymakers and Program implementers regarding their engagement in Primary Health Care delivery in Nigeria [16].…”
Section: Introductionmentioning
confidence: 99%